Women’s Role in Social Community and Regional Leadership in Madura: the role of women and regional leadership in Madura - Mohammad Sufiyanto; Alviatul Munawaroh; Siti Maghfiroh Qurrotul Aini (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
This study discusses the role of women as regional leaders, in the East Java region precisely on the island of Madura in one period. Although initially the existence of women is also often doubted and looked at in one eye, not a few of them can answer with the achievement of very glorious achievements. Success in leading an area is not determined by its gender, but rather by the utilization of the abilities and potential possessed by the person himself. This study is qualitative descriptive, namely direct observation in four regions in the districts in Madura, with interview techniques, questionnaires, and also observations. The discussion of the role of female leaders or also called